Molecular dynamics of ionic liquids confined in solid silica matrix for lithium batteries - Petit, Dominique; Korb, Jean-Pierre; Levitz, Pierre; LeBideau, Jean; Brevet, D. (Diffusion Fundamentals, 2009)
We present the first results of the magnetic field dependence of the longitudinal nuclear magnetic relaxation of anion-cation pair of ionic liquids (Li+-ionogels) confined within a silica-like mesoporous matrices designed for lithium batteries. These results are in favour of a very-correlated dynamical motion of the anion-cation pair within the solid and disordered silica matrix.